Assessment of women's benefits and constraints in participating in agroforestry exemplar landscapes - Nguyen, M.P.; North, H.; Duong, M.T.; Nguyen, M.C. (World Agroforestry Centre, 2021)
Participating in AFLi Exemplar project has positive impacts on ethnic women such as increasing their network, decision making skills, public speaking skills. However, the rate of female farmers accessing and using project extension materials or participated in project nurseries and applying agroforestry techniques remains limited. This requires understanding of the real needs and interests grounded in those socio-cultural contexts as the ethnic groups living in the Northern mountain areas in Vietnam have unique social and cultural norms and values. The case studies have shown that agricultural activities are highly gendered, in which men and women play specific roles and have different particular constraints and interests. Women are highly constrained by gender norms, access to resources, decision-making power and a prevailing positive-feedback loop of time poverty, especially in H'mong community. A holistic, time-saving approach to addressing women’s daily activities could reduce the effects of time poverty and increase project participation. As women were highly willing to share project information, project impacts would be more successful with increased participation from women by utilizing informal channels of communication and knowledge dissemination. Extension materials designed for ethnic women should have less text and more visualization. Access to information is a vital constraint that perpetuates the norm that men are decision-makers thereby enhancing their perceived ownership, where women have limited access to information and so leave final decisions to men, especially in Hmong families. Old H'mong women have Vietnamese language barrier which prevent them from accessing project materials. Further research into an adaptive framework which can be applied in a variety of contexts is recommended. This framework should prioritize time-saving activities for women and include materials highlighting key considerations to maintain accountability among project support staff.